Sensor Node for Medical Application - Ahmad, Mohd Asri (Universiti Teknologi Petronas, 2008)
Sensor network has been used in many applications namely military, medical and envirorunent. It is used to monitor and collect data from physical environment. It is used to monitor and collect data from physical envirorunent. The sensor network is basically a collection of sensor nodes usually interconnected wirelessly to perform a specific task. The aim of this project is to design and develop an automated system for medical application. The system will be using sensor nodes for collecting temperature data of the patient diagnosed with dengue fever. This system designed is to replace the current method used in hospitals to save clinicians' time and to have proper database system for future access. The sensor node system will connect patients to the PC through wireless connection mode. The temperature reading will be stored on the computer and graphs will be plotted automatically. It is envisaged that the system built will help clinicians to perform their job faster.